Efficiency of certain attractants on the Control of ceratitis capitata ( wied) - Eissa, I.S.; Hammad,Sh.M.; Abdo, A.M.I. (2005)
Experiment was conducted from November 9th 2000 till February 15th, 2001 in an navel orange grove near EI- Mamora village, Alexandria Governorate. The attractiveness of three materials polycor, Buminal and Di-ammonium hydrogenophosphate ( NH4 )2 HP04. 3% and one blank treatment were studied, with an emphasis on their possible use, as a mean to control the Med-fly ceratitis capitata ( Wied). The four treatments were studied in three replicates in a randomized block design. The fruit infestation was surveyed every week on three randomly selected trees for each replicate. The effect of temperature and humidity on trap attractancy, and the relationship between trap capture and infestation were also investigated. The attractancies were found to be strongly dependent on attractant type. For males, the highest attractancy was associated with polycor and the lowest with di-ammonium hydrogeno phosphate throughout most of the experiments. However, the infestation was at low level in the treated areas compared with the untreated.
Includes references.
Summary in Arabic.
1